Vasudevan, Alexander (2017). The Autonomous City: A History of Urban Squatting - Tutor Anton, Aritz (Documents d'Anàlisi Geogràfica, 2019)
Vasudevan, Alexander (2017) The Autonomous City: A History of Urban Squatting Londres: Verso, 304 p. ISBN 978-1781687864